The complete mitochondrial genome of the armored catfish, Hypostomus plecostomus (Siluriformes: Loricariidae). (3rd May 2016) - Liu, Shikai; Zhang, Jiaren; Yao, Jun; Liu, Zhanjiang
Abstract: The complete mitochondrial genome of the armored catfish, Hypostomus plecostomus, was determined by next generation sequencing of genomic DNA without prior sample processing or primer design. Bioinformatics analysis resulted in the entire mitochondrial genome sequence with length of 16, 523 bp. The H. plecostomus mitochondrial genome is consisted of 13 protein-coding genes, 22 tRNA genes, 2 rRNA genes, and 1 control region, showing typical circular molecule structure of mitochondrial genome as in other vertebrates. The whole genome base composition was estimated to be 31.8% A, 27.0% T, 14.6% G, and 26.6% C, with A/T bias of 58.8%. This work provided the H. plecostomus mitochondrial genome sequence which should be valuable for species identification, phylogenetic analysis and conservation genetics studies in catfishes.